Characterization of cumulus cloud fields using trajectories in the center of gravity versus water mass phase space: 1. Cloud tracking and phase space description. Issue 11 (7th June 2016) - Heiblum, Reuven H.; Altaratz, Orit; Koren, Ilan; Feingold, Graham; Kostinski, Alexander B.; Khain, Alexander P.; Ovchinnikov, Mikhail; Fredj, Erick; Dagan, Guy; Pinto, Lital; Yaish, Ricki; Chen, Qian
Abstract: We study the evolution of warm convective cloud fields using large eddy simulations of continental and trade cumulus. Individual clouds are tracked a posteriori from formation to dissipation using a 3‐D cloud‐tracking algorithm, and results are presented in the phase space of center of gravity altitude versus cloud liquid water mass (CvM space). The CvM space is shown to contain rich information on cloud field characteristics, cloud morphology, and common cloud development pathways, together facilitating a comprehensive understanding of the cloud field. In this part we show how the meteorological (thermodynamic) conditions that determine the cloud properties are projected on the CvM phase space and how changes in the initial conditions affect the clouds' trajectories in this space. This part sets the stage for a detailed microphysical analysis that will be shown in part II. Key Points: Introducing 3‐D cloud tracking and cloud center of gravity versus mass (CvM) phase space Trajectories in the CvM space reveal cloud field characteristics Cloud clustering in the CvM space shows the role of the thermodynamic profiles